Long‐term, prolonged‐release tacrolimus‐based immunosuppression in de novo kidney transplant recipients: 5‐year prospective follow‐up of the ADHERE study patients. (24th October 2019) - Rummo, Oleg; Carmellini, Mario; Kamar, Nassim; Durrbach, Antoine; Mousson, Christiane; Caputo, Flavia; Mathe, Zoltan; Christiaans, Maarten H. L.; Kuypers, Dirk R. J.; Klempnauer, Jürgen; Anaokar, Swapneel; Hurst, Martin; et al.
Summary: The objectives of this study were to assess long‐term graft survival, patient survival, renal function, and acute rejections in de novo kidney transplant recipients, treated with once‐daily prolonged‐release tacrolimus‐based therapy. The study was a 5‐year non‐interventional prospective follow‐up of patients from the ADHERE study, a Phase IV 12‐month open‐label assessment of patients randomized to receive prolonged‐release tacrolimus in combination with mycophenolate mofetil (MMF) (Arm 1) or sirolimus (Arm 2). From 838 patients in the randomized study, 587 were included in the long‐term follow‐up, of whom 510 completed the study at year 5. At 1 year post‐transplant, graft and patient survival rates were 93.0% and 97.8%, respectively, and at 5 years were 84.0% and 90.8%, respectively. Cox proportional hazards analysis showed no association between graft loss, initial randomized treatment arm, donor age, donor type, or sex. The 5‐year acute rejection‐free survival rate was 77.4%, and biopsy‐confirmed acute rejection‐free survival rate was 86.0%. Renal function remained stable over the follow‐up period: mean ± SD eGFR 4‐variable modification diet in renal disease formula (MDRD4) was 52.3 ± 21.6 ml/min/1.73 m 2 at 6 months and 52.5 ± 23.0 ml/min/1.73 m 2 at 5 years post‐transplant. These findings support the role of long‐term once‐daily prolonged‐release tacrolimus‐based immunosuppression, in combination with sirolimus or MMF, for renal transplant recipients in routine clinical practice.